L’expertise vidéo et l’analyse tactique offensive en football Etude du cas de catégories jeunes de l’équipe nationale algérienne (U17), (U20), (U23).championnats internationaux. - BAROUDI Mohamed Amine (My University, 2015)
The professional football sportive and financial games led the coaches to seek constantly for the best means of evaluation and amelioration of the performances whether individual or collective. The video analysis of the matches has become a crucial element in the processes of training and preparing for performance at a highest level. It provides a means of quantifying and qualifying the characteristics of the individual or collective performance on athletic, technical and tactics plans. The study has as a principle objective to put in evidence the video analysis of the offensive tactics according to the rapid type or of position, and to have an idea on the efficiency of the each type of attack used during the championships of Africa (U17), (U20) and the pre-Olympic sessions (U23). The results of this study show the existence of non significant differences between the two types of attacks and the level of efficiency, we notice that there is no significant differences between success and failure in (U17) under the age of 17 and (U20) under the age of 20. However, we found a highly significant difference between failure and success concerning the effectiveness in (U23) under the age of 23. What‘s more interesting in this study is do show that the adopted styles by the young Algerian games is in the adoption of a game which doesn‘t cope with the Algerian temper, but it convenes to the international norms which prefers adopting a certain equal alternation between the two styles, the direct style and the indirect one. Finally, we believe that such a study can elaborate further analyses on other age categories and other variables, as well as the integration of modern computer technology in the Algerian football.
Keywords: Analysis- Offensive tactics- video- football.